A Study on the Distribution of One Way Packs of Hindustan Coca Cola Beverages in Vijayawada City - Prasad, Ayatham (Indian Journal of Marketing, 2006)
The manufacturing of soft drinks began in the 1830’s. However, the evolution of soft drinks took place over a much longer time period. The forerunners of soft drinks began more than 2,000 years ago when Hippocrates, the "Father of Medicine," first suspected that mineral waters could be beneficial to our well-being. The soft drink industry was a seasonal business in the early days, operating primarily during the summer months. Gradually, demand grew for soft drinks to be consumed in the home. Automatic vending machines began to appear in the 1920’s, once again changing the business of soft drinks. Vending machines and fountain dispensers led the way to the expansion of soft drinks to industrial outlets.